ANALISIS PERHITUNGAN BIAYA SATUAN TINDAKAN ORIF (Open Reduction Internal Fixation) FRAKTUR FEMUR MENGGUNAKAN METODE ABC (Activity Based Costing) (STUDI KASUS DI RS PKU MUHAMMADIYAH BANTUL) - Rizka Nurul Firdaus; Firman Pribadi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2015)
Background: The determination of operating room rates at PKU Muhammadiyah Hospital in Bantul is currently using fee for service method where the operating rate is determined by the calculation of the cost components that occur as the cost of medical services, consumables, medicines, and the rent of operating room, but it has not included all the components of the activity-based costs associated with clinical pathways. However, this surgical procedure may result significant costs to the hospital. Methods: The study was conducted at PKU Muhammadiyah Hospital in Bantul. This research is descriptive qualitative case study design. The sample were the patients who underwent an operation of ORIF for Femoral Fractures without complications that met the inclusion and exclusion criteria. Cost analysis method used was the Activity-Based Costing (ABC). Results and Discussion: The unit cost of ORIF for Femoral Fractures which was calculated by the method of Activity Based Costing (ABC) was 8,157,726 rupiahs, while the real cost spent by the hospital was 9,035,885 rupiahs. The amount of real cost on ORIF for Femoral Fracture specified by RS PKU Muhammadiyah Bantul was higher than the unit cost calculated based on Activity-Based Costing method. The obtained difference was a positive difference, which was 878.159 rupiahs (10,76%). In the Activity-Based Costing (ABC), indirect and direct cost (overhead) are charged at some cost drivers, while the traditional system is only charged on a cost driver. Conclusions and Recommendations: Based on the calculation of unit costs obtained, it can be concluded that the unit cost of ORIF for Femoral Fracture in Central Surgery Installation PKU Muhammadiyah Hospital in Bantul with Activity- Based Costing method is lower and more proportionate with the activity. However, the hospital should also apply the calculation of the unit cost to all the types of service especially for surgery in order to identify and examine the cost components which are subject to change at any time and cause some disadvantages to the hospital accounting.